Developing English Reading Material for the Second Grade of Vocational High School - Arif Widyantoro (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2021)
The purpose of this study are to describe how to develop English reading materials for the second grade of Vocational High School and to explain the advantages and disadvantages of developing English reading materials for the second grade of vocational high school. Using English reading material for developing the students’ ability of the second grade of vocational high school is one of the ways to make the students interested in learning English. In teaching English reading materials, this paper applies two phases (planning phase, implementing phase, evaluating phase) and PQRST (Preview, Question, Read, Summarize, Test) method. The advantages of developing English reading material for the second grade of vocational high school are: It can develop their vocabulary and grammar mastery. It is described that using reading materials in developing the students’ proficiency of English is very beneficial. The students get the systematic, effective, and efficient learning method, and also they can enjoy the teaching learning process. Encourage the student to improve their previous background knowledge of fundamental concepts. It can motivate the Students to actively reflect upon the material being studied prior to its presentation in class and to search for explanations or solutions on their own. While, the disadvantages are: It cannot develop the listening skill directly; It may happen that the students did not understand clearly about the generic structure and language feature of the text if they just pay attention with the meaning of each word. The writer hopes that this paper can be used as a reference for the teachers who want to improve their students’ ability, especially in reading ability. Furthermore, it can be a reference for the students of English department who want to write a paper or a thesis. Keywords: English Language, Reading, Vocational High School